2016
DOI: 10.1038/ncomms13674
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting protein regulates haematopoietic stem cell ageing and rejuvenation by inhibiting p38 kinase activity

Abstract: Ageing is a natural process in living organisms throughout their lifetime, and most elderly people suffer from ageing-associated diseases. One suggested way to tackle such diseases is to rejuvenate stem cells, which also undergo ageing. Here we report that the thioredoxin-interacting protein (TXNIP)-p38 mitogen-activated protein kinase (p38) axis regulates the ageing of haematopoietic stem cells (HSCs), by causing a higher frequency of long-term HSCs, lineage skewing, a decrease in engraftment, an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 50 publications
0
59
0
Order By: Relevance
“…However, the interaction of TXNIP and AKT was upregulated by glucose and H 2 O 2 treatment (Figure 3), implying that TXNIP may negatively regulate AKT activity under glucose stress and oxidative stress. We previously reported that TXNIP deficiency induced premature aging phenotypes of HSCs in aged mice by increasing ROS levels in vitro and in vivo (Jung et al, 2016, 2013 ). Next, we analyzed the metabolic characterization of WT and KO mice to determine the effect of TXNIP on the aging of mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the interaction of TXNIP and AKT was upregulated by glucose and H 2 O 2 treatment (Figure 3), implying that TXNIP may negatively regulate AKT activity under glucose stress and oxidative stress. We previously reported that TXNIP deficiency induced premature aging phenotypes of HSCs in aged mice by increasing ROS levels in vitro and in vivo (Jung et al, 2016, 2013 ). Next, we analyzed the metabolic characterization of WT and KO mice to determine the effect of TXNIP on the aging of mice.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous reports, we found that TXNIP interacts with p53, p38 MAPK, and macrophage migration inhibitory factor (MIF) and regulates their functional activity (Jung et al, 2016, 2013; Kim et al, 2017). TXNIP stabilized p53 protein via direct interaction, and TXNIP acted as a functional switch of p53 to regulate ROS level in hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations